2021
DOI: 10.1002/pi.6205
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of ordered macroporous molecularly imprinted polymers and their applications in purifying cinchona alkaloids from cinchona extract

Abstract: Three‐dimensionally ordered macroporous molecularly imprinted polymers (3DOM MIPs) were prepared for the direct purification of cinchona alkaloids from crude cinchona extract. The 3DOM MIPs were easily prepared by grafting quinine‐MIPs on the pore walls of 3DOM thiol‐group‐functionalized silica. The materials were characterized using various techniques. The results showed that the 3DOM MIPs had a more regular macroporous structure, a greater surface area and a greater porosity than traditional bulk MIPs (TBMIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Zhang and colleagues prepared MIPs to separate bilobalide and ginkgolide B 13–15 . Studies have shown that MIP adsorbents are superior to commercially available conventional adsorbents such as C18, SiO 2 and macroporous resins in the selective separation of natural products 12,19 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang and colleagues prepared MIPs to separate bilobalide and ginkgolide B 13–15 . Studies have shown that MIP adsorbents are superior to commercially available conventional adsorbents such as C18, SiO 2 and macroporous resins in the selective separation of natural products 12,19 …”
Section: Introductionmentioning
confidence: 99%
“…MIPs also have the advantages of easy storage, high mechanical strength, and resistance to pH changes. Therefore, MIPs are widely applied in the fields of separation, [11][12][13][14][15] sensors 16,17 and drug delivery. 18 Recently, MIPs have been developed for the separation of active ingredients from Ginkgo biloba.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation